2001
DOI: 10.4265/bio.6.107
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Bactericidal Activity and the Hydrophobicity-Hydrophilicity Balance of Alcohol Solutions.

Abstract: Alcohols showed bactericidal activity against Staphylococcus aureus, Micrococcus luteus, Escherichia coli, and Enterobacter cloacae suspended in 0.85% (v/v) saline in the order of n-butanol>n-propanol>ethanol>methanol.Against the bacteria suspended in n-octane, however, alcohols showed a reverse order of bactericidal effectiveness.When toluene as a hydrophobic solvent was mixed with a small amount of hydrophilic methanol (5 or 10%, v/v) , or conversely, when hydrophilic methanol was mixed with a small amount o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
2
2
0
Order By: Relevance
“…Despite these differences, all the wipes had similar bactericidal activity, which did not meet the EN 16615 benchmark. Wipes C, containing propan-1-ol and propan-2-ol, had the highest bactericidal activity (against P. aeruginosa ), which is consistent with earlier reports [19,20]. Similar to previous studies, we found that Gram-negative bacteria were more susceptible to alcohol than were Gram-positive bacteria [17,19].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Despite these differences, all the wipes had similar bactericidal activity, which did not meet the EN 16615 benchmark. Wipes C, containing propan-1-ol and propan-2-ol, had the highest bactericidal activity (against P. aeruginosa ), which is consistent with earlier reports [19,20]. Similar to previous studies, we found that Gram-negative bacteria were more susceptible to alcohol than were Gram-positive bacteria [17,19].…”
Section: Discussionsupporting
confidence: 92%
“…Wipes C, containing propan-1-ol and propan-2-ol, had the highest bactericidal activity (against P. aeruginosa ), which is consistent with earlier reports [19,20]. Similar to previous studies, we found that Gram-negative bacteria were more susceptible to alcohol than were Gram-positive bacteria [17,19]. Andersen et al showed that the bacterial reduction with ethanol wipes did not meet the EN 16615 benchmark (< 3 lg) [21].…”
Section: Discussionsupporting
confidence: 92%
“…While little is known about the specific bactericidal mechanism of ethanol, it is generally hypothesized that the solvent targets the cell membrane, causing catastrophic damage to the phospholipid layers, as well as intracellular proteins, leading to irreversible denaturation of these biomolecules [ 7 ]. As such, the inclusion of water molecules at 30% - 40% v/v helps to optimize the hydrophobicity-hydrophilicity balance of the ethanol, allowing better penetration of the chemical entity into and/or through the bacterial cell membrane [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Based on CDC's requirement, an effective alcohol-based sanitizer should contain at least 60% alcohol [3][4][5]. A study by Masaru et al showed that the effect of ethanol concentration on bactericidal potency follows a U-shape profile, where antibacterial functionalities improved with increasing ethanol concentration before dipping drastically at 100% ethanol [6]. This could be attributed to the bactericidal mechanism of ethanol.…”
Section: Introductionmentioning
confidence: 99%